In situ experimental study on the effect of mixed inhibitors on the phase equilibrium of carbon dioxide hydrate. (2nd February 2022) - Li, Yan; Chen, Jiangzhi; Maria Gambelli, Alberto; Zhao, Xia; Gao, Yue; Rossi, Federico; Mei, Shenghua
Highlights: Quantified the inhibition effect of mixed inhibitor (electrolyte plus alcohol) on CO2 hydrate; In-situ study on the CO2 -H2 O– electrolyte -alcohol system in high-pressure optical cell; The binding mode of CO2 hydrate was observed by Raman spectroscopy; An improved van der Waals Platteeuw (vdW-P) model is proposed to predict the stability conditions of hydrate in the CO2  + H2 O + inhibitor solution. Abstract: Electrolytes and alcohols are two thermodynamic inhibitors commonly used to prevent hydrate growth in gas and oil pipelines in the gas industry. Although the phase behavior of CO2 hydrate in the presence of electrolyte and/or alcohol has been extensively studied, the knowledge of the combined effect of these two as mixed inhibitors on CO2 hydrate is still very limited. In this study, the influence of mixed inhibitors comprising an electrolyte (selected from sodium chloride and calcium chloride) mixed with an alcohol (selected from methanol, ethanol, ethylene glycol, n-propanol, and isopropanol) on the thermodynamic properties of carbon dioxide hydrate was investigated. Observations on CO2 -H2 O-NaCl-alcohol system were performed using high-pressure optical cell (HPOC) technology. The experiments were carried out at low temperatures of 263–283 K and high pressures up to 4 MPa, focusing on the phase equilibrium of liquid, hydrate, and carbon dioxide gas in HPOC. Experimental results reveal that the inhibition strength of the mixed inhibitor is clearly enhanced; in some cases, the inhibition intensity of the mixed inhibitor is greater than the sum of its components because of the synergistic effect. For example, under a pressure of ∼ 2 MPa, the temperature depressions of 10 wt% methanol and 10 wt% sodium chloride for CO2 hydrate are 4.53 K and 4.87 K, respectively; the mixture of these two can produce a temperature depression as high as 12.53 K. Our results also show that the inhibition strength of the inhibitor, single or mixed, increases with the pressure. Based on our results, an improved van der Waals Platteeuw (vdWP) model is proposed to predict the hydrate stability conditions in the CO2 -H2 O-inhibitor solution. Results from this study provide a ground for a better understanding of the thermodynamic properties of carbon dioxide hydrate under extreme conditions.